Mortality and cardiovascular and respiratory morbidity in individuals with impaired FEV1 (PURE): an international, community-based cohort study - Duong, MyLinh; Islam, Shofiqul; Rangarajan, Sumathy; Leong, Darryl; Kurmi, Om; Teo, Koon; Killian, Kieran; Dagenais, Gilles; Lear, Scott; Wielgosz, Andreas; Nair, Sanjeev; Mohan, Viswanathan; et al. (The Lancet global health, 2019)
The associations between the extent of forced expiratory volume in 1 s (FEV1) impairment and mortality, incident cardiovascular disease, and respiratory hospitalisations are unclear, and how these associations might vary across populations is unknown. In this international, community-based cohort study, we prospectively enrolled adults aged 35–70 years who had no intention of moving residences for 4 years from rural and urban communities across 17 countries. A portable spirometer was used to assess FEV1. FEV1 values were standardised within countries for height, age, and sex, and expressed as a percentage of the country-specific predicted FEV1 value (FEV1%). FEV1% was categorised as no impairment (FEV1% ≥0 SD from country-specific mean), mild impairment (FEV1% <0 SD to −1 SD), moderate impairment (FEV1% <–1 SD to −2 SDs), and severe impairment (FEV1% <–2 SDs [ie, clinically abnormal range]). Follow-up was done every 3 years to collect information on mortality, cardiovascular disease outcomes (including myocardial infarction, stroke, sudden death, or congestive heart failure), and respiratory hospitalisations (from chronic obstructive pulmonary disease, asthma, pneumonia, tuberculosis, or other pulmonary conditions). Fully adjusted hazard ratios (HRs) were calculated by multilevel Cox regression. Among 126 359 adults with acceptable spirometry data available, during a median 7·8 years (IQR 5·6–9·5) of follow-up, 5488 (4·3%) deaths, 5734 (4·5%) cardiovascular disease events, and 1948 (1·5%) respiratory hospitalisation events occurred. Relative to the no impairment group, mild to severe FEV1% impairments were associated with graded increases in mortality (HR 1·27 [95% CI 1·18–1·36] for mild, 1·74 [1·60–1·90] for moderate, and 2·54 [2·26–2·86] for severe impairment), cardiovascular disease (1·18 [1·10–1·26], 1·39 [1·28–1·51], 2·02 [1·75–2·32]), and respiratory hospitalisation (1·39 [1·24–1·56], 2·02 [1·75–2·32], 2·97 [2·45–3·60]), and this pattern persisted in subgroup analyses considering country income level and various baseline risk factors. Population-attributable risk for mortality (adjusted for age, sex, and country income) from mildly to moderately reduced FEV1% (24·7% [22·2–27·2]) was larger than that from severely reduced FEV1% (3·7% [2·1–5·2]) and from tobacco use (19·7% [17·2–22·3]), previous cardiovascular disease (5·5% [4·5–6·5]), and hypertension (17·1% [14·6–19·6]). Population-attributable risk for cardiovascular disease from mildly to moderately reduced FEV1 was 17·3% (14·8–19·7), second only to the contribution of hypertension (30·1% [27·6–32·5]). FEV1 is an independent and generalisable predictor of mortality, cardiovascular disease, and respiratory hospitalisation, even across the clinically normal range (mild to moderate impairment). Population Health Research Institute, the Canadian Institutes of Health Research, Heart and Stroke Foundation of Ontario, Ontario Ministry of Health and Long-Term Care, AstraZeneca, Sanofi-Aventis, Boehringer Ingelheim, Servier, and GlaxoSmithKline, Novartis, and King Pharma. Additional funders are listed in the appendix.